How to Improve Communicative Competence in a Lingua Franca: Reasons and Practices (Sains Humanika, 2017)
This paper has two aims: a) to describe how English is used as a lingua franca in Asia, and b) to discuss factors that are essential for successfully running a course collaboratively between two universities in different countries. First, I illustrate the ELT situation in Japan and hypothetical but plausible conversations among interlocutors with different proficiencies. Then, I present the conditions under which Japanese and Malaysian (or other) universities can implement an effective joint course where students can be expected to acquire genuine ‘communicative competence.’ I argue that relatively more proficient learners must make a concerted effort to engage in communicative activities in order for their less proficient interlocutors to persist in communicating in the lingua franca. Furthermore, all English speakers, whether they speak it as a foreign, second or even first language, should cultivate chances to interact with speakers with varied language backgrounds.
Keywords: Communicative competernce; power in communication; collaboration among institutes